2023
DOI: 10.1002/bem.22439
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of global DNA methylation changes in human keratinocytes immediately following exposure to a 900 MHz radiofrequency field

Abstract: The increasing use of nonionizing radiofrequency electromagnetic fields (RF-EMFs) in a wide range of technologies necessitates studies to further understanding of biological effects from exposures to such forms of electromagnetic fields. While previous studies have described mechanisms for cellular changes occurring following exposure to low-intensity RF-EMFs, the role of molecular epigenetics has not been thoroughly investigated. Specifically unresolved is the effect of RF-EMFs on deoxyribonucleic acid (DNA) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Intermittent exposure (5 min on/30 min off) to a SAR of 1.5 W/Kg 1.71 GHz RF-EMF did not induce any significant cellular dysfunction in mouse embryonic stem cell-derived neural progenitor cells [ 13 ]. In addition, exposure to 900 MHz at 40 V/m for 1 h had no significant effect on the viability of human epidermal keratinocytes [ 14 ]. Exposure to 27.1 MHz RF-EMF did not influence the viability of the human keratinocyte cell line, HaCaT [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intermittent exposure (5 min on/30 min off) to a SAR of 1.5 W/Kg 1.71 GHz RF-EMF did not induce any significant cellular dysfunction in mouse embryonic stem cell-derived neural progenitor cells [ 13 ]. In addition, exposure to 900 MHz at 40 V/m for 1 h had no significant effect on the viability of human epidermal keratinocytes [ 14 ]. Exposure to 27.1 MHz RF-EMF did not influence the viability of the human keratinocyte cell line, HaCaT [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Intermittent exposure (5 min on/30 min off) to SAR of 1.5 W/Kg 1.71 GHz RF-EMF did not induce any significant cellular dysfunction in mouse embryonic stem cell-derived neural progenitor cells [11]. In addition, exposure to 900 MHz at 40 V/m for 1 h had no significant effect on the viability of human epidermal keratinocytes [12]. Exposure to 27.1 MHz RF-EMF did not influence the viability of the human keratinocyte cell line, HaCaT [13].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the U.S. Air Force Research Laboratory reported that whole-genome bisulfite sequencing directly following RF exposure showed immediate changes in DNA methylation patterns and early differentially methylated genes in RF-electromagnetic field-exposed keratinocytes in human skin [1]. The results highlight a potential epigenetic role in the cellular response to RF radiation.…”
mentioning
confidence: 95%